Progressive Leadership in Primary Education of Kartasura in the Era Global Computing - Susanti, Irin Dwi; Prayitno, Harun Joko; Haryanto, Sigit; Muhibbin, Ahmad (Graduate Program Magister Manajemen Pendidikan, 2023)
The condition of education is an increasingly advanced technology; teachers are required to be able to keep up with the development of information and communication. Thinking about the importance of educational leadership is seen as the most important need. This research aims to find out how leaders try to influence group members about specific situations. This research was conducted using the descriptive qualitative method with a case study design. The research subjects were the principal, curriculum principal, student affairs vice principal, and teachers. Data collection techniques were interviews, observation, and documentation. Data validity checking techniques were carried out using triangulation techniques and sources. Data analysis techniques were carried out with data reduction steps, data presentation, and conclusion drawing). The results showed that: progressive educational leadership strategies in facilitating change and innovation in schools conducted workshops for teachers of all subjects and the principal’s implementation in the educational evaluation was conducted active weekly.